Cooperation of Oligodeoxynucleotides and Synthetic Molecules as Enhanced Immune Modulators - Nigar, Shireen; Shimosato, Takeshi (Frontiers in Nutrition, 2019)
Unmethylated cytosine–guanine dinucleotide (CpG) motifs are potent stimulators of the host immune response. Cellular recognition of CpG motifs occurs via Toll-like receptor 9 (TLR9), which normally activates immune responses to pathogen-associated molecular patterns (PAMPs) indicative of infection. Oligodeoxynucleotides (ODNs) containing unmethylated CpGs mimic the immunostimulatory activity of viral/microbial DNA. Synthetic ODNs harboring CpG motifs resembling those identified in viral/microbial DNA trigger an identical response, such that these immunomodulatory ODNs have therapeutic potential. CpG DNA has been investigated as an agent for the management of malignancy, asthma, allergy, and contagious diseases, and as an adjuvant in immunotherapy. In this review, we discuss the potential synergy between synthetic ODNs and other synthetic molecules and their immunomodulatory effects. We also summarize the different synthetic molecules that function as immune modulators and outline the phenomenon of TLR-mediated immune responses. We previously reported a novel synthetic ODN that acts synergistically with other synthetic molecules (including CpG ODNs, the synthetic triacylated lipopeptide Pam3CSK4, lipopolysaccharide, and zymosan) that could serve as an immune therapy. Additionally, several clinical trials have evaluated the use of CpG ODNs with other immune factors such as granulocyte-macrophage colony-stimulating factor, cytokines, and both endosomal and cell-surface TLR ligands as adjuvants for the augmentation of vaccine activity. Furthermore, we discuss the structural recognition of ODNs by TLRs and the mechanism of functional modulation of TLRs in the context of the potential application of ODNs as wide-spectrum therapeutic agents.